Strategi Penguatan Kerja Sama Trimatra Terpadu Tni Untuk Mencegah Kejahatan Non Tradisional Lintas Negara - Safrudin, Muhammad Nur; Harsono, Gentio; Subiantoro , Yudi (Syntax Corporation, 2025)
The increasingly dynamic global strategic environment has generated various forms of non-traditional transnational threats, such as narcotics trafficking, human trafficking, cybercrime, and maritime terrorism. This situation requires the Indonesian National Armed Forces (TNI) to strengthen synergy and enhance the effectiveness of Tri-Service cooperation in responding to threats that are multidimensional and cross-domain in nature. However, the implementation of Integrated Tri-Service Cooperation still encounters a number of challenges, particularly in the aspects of command structure, system interoperability, organizational culture, and resource support. This study aims to formulate effective, integrated, and sustainable strategies to strengthen TNI Tri-Service cooperation in preventing non-traditional transnational crimes. The research employs a quasi-quantitative approach by combining Strengths, Weaknesses, Opportunities, and Threats (SWOT) analysis to formulate strategies, followed by the Analytical Hierarchy Process (AHP) to determine strategic priorities. The findings of this study highlight four key points. First, five major inhibiting factors were identified: limited interoperability, the absence of a permanent joint command structure, sectoral ego and differing organizational cultures, weak regulatory and legal authority, and limitations in budget and logistics. Second, six priority strategies were formulated: strengthening cross-service C4ISR systems, fostering a collaborative work culture and joint discipline, developing a Joint Command Information System (JCIS), establishing a permanent Joint Training Center (JTC), forming a permanent Tri-Service joint command structure, and developing a digital-based joint logistics system. Third, the priority ranking of these strategies is: strengthening cross-service C4ISR systems (0.261), forming a permanent Tri-Service joint command structure (0.174), developing JCIS (0.174), developing a digital joint logistics system (0.147), establishing a permanent JTC (0.134), and fostering collaborative work culture and joint discipline (0.109). Fourth, this study establishes a comprehensive and adaptive strategic model in which the integration of C4ISR–JCIS systems serves as the core of interoperability, strengthened by a permanent command structure, digital joint logistics, and a cross-service collaborative culture as the foundation for sustainable TNI synergy.